Miconazole induces aneuploidy-mediated tolerance in Candida albicans that is dependent on Hsp90 and calcineurin - Guo, Liangsheng; Zheng, Lijun; Dong, Yubo; Wang, Chen; Deng, Huijie; Wang, Zongjie; Xu, Yi (Frontiers in Cellular and Infection Microbiology, 2024)
Antifungal resistance and antifungal tolerance are two distinct terms that describe different cellular responses to drugs. Antifungal resistance describes the ability of a fungus to grow above the minimal inhibitory concentration (MIC) of a drug. Antifungal tolerance describes the ability of drug susceptible strains to grow slowly at inhibitory drug concentrations. Recent studies indicate antifungal resistance and tolerance have distinct evolutionary trajectories. Superficial candidiasis bothers millions of people yearly. Miconazole has been used for topical treatment of yeast infections for over 40 years. Yet, fungal resistance to miconazole remains relatively low. Here we found different clinical isolates of Candida albicans had different profile of tolerance to miconazole, and the tolerance was modulated by physiological factors including temperature and medium composition. Exposure of non-tolerant strains with different genetic backgrounds to miconazole mainly induced development of tolerance, not resistance, and the tolerance was mainly due to whole chromosomal or segmental amplification of chromosome R. The efflux gene CDR1 was required for maintenance of tolerance in wild type strains but not required for gain of aneuploidy-mediated tolerance. Heat shock protein Hsp90 and calcineurin were essential for maintenance as well as gain of tolerance. Our study indicates development of aneuploidy-mediated tolerance, not resistance, is the predominant mechanism of rapid adaptation to miconazole in C. albicans, and the clinical relevance of tolerance deserves further investigations.